Strategy of the Department of Industry In Improving Industrial Development - Burhanudin Burhanudin; Muhammad Reza Fahlevy; Fauziah Fitriyani (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
The purpose of this study is to describe and analyze the strategy of the Department of Industry in Improving Industrial Development in Samarinda City. The data collection technique in this study was obtained using the Purposive Sampling technique. The data analysis used in this study is qualitatively descriptive which aims to describe in depth the strategy of the Industrial Service in Improving Industrial Development in Samarinda City. Interactive model data analysis, which begins with data reduction, data presentation, data condensation, and conclusion drawing/verification. The results of this study show that the Samarinda City Industrial Office has carried out efforts with technical guidance, improving local bran, improving packaging, establishing permit and halal regulations. This can be seen to provide motivation and skill improvement for Small and Medium Industry personnel.